Uso de abordagem heurística para o problema do quadro de horários e alocação de salas de aula - Silveira, Jhonathan Alberto dos Santos (2018)
This study is about the problem to elaborate the teachers’ timetabling and the classroom assignment in Instituto Federal Farroupilha - Campus Avançado Uruguaiana. This task is already known because of its complexity and the necessity to reconcilie many resources, like teachers, classes, classrooms, among others. This process, is usually manually solved by the educational institutions, it can take many days to be complited, besides being a hard and delayed job, many times it doesn’t ensure a good solution. The objective of this job is to develop a new timetabling and classroom allocation in order to better meet the constraints of the problem. To do it, it will be accomplished a greedy constructive procedure to find the initial solution and right after it, it will be applied a metaheuristic called Tabu Search as an enhancement way to the found solution. Besides, it will be developed an iterative software to build and manage this task.